Influence of Family-Work Balance Conflict on Female Principals’ Managerial Duties in Public Secondary Schools in Machakos County, Kenya - Mbithuka, Miriam; Muola, James; Maithya, Redempta (The International Journal Of Humanities & Social Studies, 2017)
The purpose of this study was to establish the influence of family-work balance conflicts on female principals’ willingness to take up managerial duties in public secondary schools in Kathiani Sub-County in Machakos County. The target population for the study consisted of all the female principals, female deputy principals, and female teachers from public secondary schools in Kathiani Sub-County. The sample size was 127 respondents of the target population. Descriptive survey design was employed in order to address the study objectives via the specified hypotheses. The study found that family responsibilities prevent female teachers from applying for principal ship. In addition, the study found that doubling as a mother and a career woman is not easy and especially when one has to be in school very early in the morning. However, the study also found that with proper time management there is no conflict between domestic and professional roles for female principals. Hence, effective ways of managing stress reduces the pressure from both domestic and professional roles. The study recommends that female teachers, deputy principals and principals need to be trained on proper time management to ensure there is no conflict between domestic and professional roles for female principals.
Keywords: Family-work balance; conflicts; female principals; managerial duties